Tereza Novotná: How Germany Unified and the EU Enlarged: Negotiating the Accession through Transplantation and Adaptation (Czech Journal of International Relations, 2016)
Tereza Novotná: How Germany Unified and the EU Enlarged: Negotiating the Accession through Transplantation and Adaptation. 1. vydání. Basingstoke: Palgrave Macmillan, 2015, 235 stran, ISBN 978-1-137-47760-6 (signatura knihovny ÚMV 61 427).